Management Practices to Control Tropical Soda Apple - Jeff Mullahey; Pat Hogue (EDIS)
Tropical soda apple (TSA) is a serious weed problem in many pastures throughout Florida. If not controlled, pasture production (yield) declines resulting in lower stocking rates, lower forage quality, and ultimately, lower ranch profitability. What is the game plan when it comes to controlling TSA? This document is WEC 177, one of a series of the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: May, 2003.